2015
DOI: 10.1007/s00408-015-9792-9
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Adherence to the Mediterranean Diet and Asthma in Peruvian Children

Abstract: PurposeAdherence to a Mediterranean diet pattern may be associated with lower asthma prevalence in children. We sought to corroborate these findings in Peruvian children.MethodsThis case–control study included children of ages 9–19 years living in Lima, Peru. A food frequency questionnaire (FFQ) was completed and diet pattern was analyzed using a modified Mediterranean diet score (MDS). Primary analysis investigated the relationship between MDS and asthma status. Maternal education, age, sex, and body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 31 publications
3
62
0
2
Order By: Relevance
“…Some studies showed a small but positive effect on current severe asthma in girls 105 and a protective effect on asthma/ wheeze. 69,96,100,110 Alternatively, some studies showed no protective effect on asthma and/or rhinitis symptoms 98,99,108,109 or atopic dermatitis. 97 None of the studies reported on food allergy as an outcome.…”
Section: Mediterranean Diet In Infancy and Childhoodmentioning
confidence: 99%
“…Some studies showed a small but positive effect on current severe asthma in girls 105 and a protective effect on asthma/ wheeze. 69,96,100,110 Alternatively, some studies showed no protective effect on asthma and/or rhinitis symptoms 98,99,108,109 or atopic dermatitis. 97 None of the studies reported on food allergy as an outcome.…”
Section: Mediterranean Diet In Infancy and Childhoodmentioning
confidence: 99%
“…Breastfeeding 51,52 and the Mediterranean diet 53,54 have each been associated to lower risk of both obesity and asthma. We recently described that a diet abundant in sweets and dairy products is associated with increased asthma risk (and with higher serum IL-17F), while frequent consumption of vegetables and grains was linked to lower odds of asthma 55 .…”
Section: Diet and Nutrientsmentioning
confidence: 99%
“…It is traditionally practiced in countries of the Mediterranean basin, especially Greece, Italy, and Spain (1). Described benefits included cardiovascular diseases prevention (2), reversion of the metabolic syndrome (3), prevention of the invasive breast cancer (4), prostate (5), and colorectal cancer (6), prevention of the age-related cognitive decline (7), and even a protective role in asthma among children (8,9). Additionally, in Swedish population a 2-year survival increase was observed among people with higher compliance with the Mediterranean diet (10).…”
mentioning
confidence: 99%